(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
To improve the applications of ZnO, metal ion doping is found to be the most effective approach which induces structural modifications. Doping changes the optical, magnetic and electrical properties of nanoparticles due to this the nanoparticles are doped with metals like Fe, Cd, Mn, Ni, Al, etc. But here we mainly analyse the Cd doped ZnO nanoparticles.Preparation of doped materials such as the Cd doped ZnO are important for creating a new combinations to form a substance of modified optical properties. Electrical conduction has been found to increase for higher concentration of Cd in ZnO which can be useful in the various optoelectric devices such as Solar cells, LEDs, Light absorption and emission, Photodiodes, Laser diodes.